Simulation and Assessment of Thermal-Stress Analysis of Welding Materials in IGBT - Yang Yang; Jibing Chen; Bowen Liu; Yiping Wu (Micromachines)
Insulated gate bipolar transistors (IGBTs), as an important power semiconductor device, are susceptible to thermal stress, thermal fatigue, and mechanical stresses under high-voltage, high-current, and high-power conditions. Elevated heat dissipation within the module leads to fluctuating rises in temperature that accelerate its own degradation and failure, ultimately causing damage to the module as a whole and posing a threat to operator safety. Through ANSYS Workbench simulation analysis, it is possible to accurately predict the temperature distribution, equivalent stress, and equivalent strain of solder materials under actual working conditions, thus revealing the changing laws of the heat–mechanical interaction in solder materials. Simulation analysis results show that, under steady-state operating conditions, the highest point of the IGBT module’s overall junction temperature occurs in the center of the chip. Nanogold exhibited the best performance in terms of temperature and equivalent stress-strain among the five solders studied in this paper; defects near the edges caused greater harm to the module compared to those closer to the solder layer’s center. In terms of stress, defects located near the edge corners produced larger strains. Crazing damage in joints allows for a faster transfer of heat sources away from the center; in terms of stress, crazing has fewer detrimental effects on the integrity of the module as compared to through cracks. Simulation analysis can model the interaction of heat and equipment under realistic work conditions, comparing and evaluating different types of solder materials to select the most suitable solder material for product design and material selection. This aids in enhancing design precision and reliability.